Spindle-shaped efficient adsorbent NiCo2O4/MIL-53(Fe) for the removal of Congo red: Design, synthesis and performance studies - Bai Sun; Taoyou Zhou; Angang Hu; Yuxian Guo; Yun Wang; Lining Bao; Hao Huang; Mingjian Yi; Shuguang Zhu; Lingtao Kong (Desalination and Water Treatment)
Novel NiCo2O4/MIL-53 (Fe) nanocomposites were synthesized by a hydrothermal preparation approach, which was employed as for the elimination of Congo red (CR) from azo dye effluents. The topography, elemental composition and crystal structure of the adsorbent were explored using SEM, EDS, XRD, FT-IR and XPS methods. The influence of different amounts of adsorbent, different ratios of Co-Fe, pH, and the presence of other anions on the adsorption performance of CR was explored. Models such as particle diffusion and pseudo second-order were successful in elucidating the adsorption kinetics of the adsorbent. Meanwhile, the Langmuir model effectively elucidated the isothermal process. The largest sorption capacity of the adsorbent for CR can reach 900.91 mg/g. Despite five cycles of recycling, the removal ratio of the adsorbent is still as high as 89.28 %, which indicates the adsorbent has an excellent reusability and recyclability. The adsorption process consists of three successive phases, focusing mainly on the key roles of monolayer adsorption and chemisorption. It provides an extensive research on the adsorption mechanism of CR, emphasizing the importance of electrostatic interactions, hydrogen bonding, metal coordination and ion exchange processes. In summary, NiCo2O4/MIL-53 (Fe) adsorbent has potential application prospects.